Arsenic contamination in groundwater in Bangladesh: implications and challenges for healthcare policy - Ahmad SA; Khan MH; Haque M (Dove Medical Press, 2018)
Sk Akhtar Ahmad,1 Manzurul Haque Khan,2 Mushfiqul Haque2 1Department of Occupational and Environmental Health, Bangladesh University of Health Sciences, Mirpur, Dhaka 1216, Bangladesh; 2Department of Occupational and Environmental Health, National Institute of Preventive Medicine, Mohakhali, Dhaka 1212, Bangladesh Abstract: Arsenic contamination of groundwater in Bangladesh has been recognized as a major public problem. The arsenic contamination was first identified in the tubewell water in 1993 in a northern district of Bangladesh. Tubewells are the main source of drinking water in rural areas, and except hilly and terrace upland throughout the Bangladesh, the arsenic-contaminated tubewells are distributed. Fifty million people of Bangladesh were estimated to be at risk of exposure to arsenic through consumption of water from contaminated tubewells. Chronic exposure to arsenic causes arsenicosis and may include multi-organ pathologies. Many of the health effects of chronic toxicity are evident in Bangladesh. Besides dermatological manifestations, noncommunicable diseases including cancer, adverse pregnancy outcomes, and decreased intelligence quotient among the children are reported to be increasing. Cancer due to long-term low-dose arsenic exposure through consumption of contaminated water is now an important concern of Bangladesh as it is being increasingly reported from arsenic-exposed individuals. Stoppage of consumption of the arsenic-contaminated water is the mainstay of arsenicosis prevention and case management. At present, a higher proportion of the people are still consuming arsenic-contaminated water because of the lack of sustainable arsenic-safe water supply. In providing sustainable arsenic-safe water options, any option advocated should be cheap, easy to use, locally maintainable, and owned by the community. In addressing arsenic-related health issues, arsenic-exposed population needs to be brought under the coverage of the regular surveillance program for detection and subsequent management of noncommunicable diseases and cancers. Keywords: arsenic, arsenic contamination, ground water, tubewell, arsenicosis, Bangladesh